دور العائلةومسؤوليتها في التعليم والتربية في ضوء سيرة الرسولﷺ: Role of family and its responsibility of education and upbringing in the light of Seerah of the Prophet Muhammad P.B.U.H - Dr. Amjad Hayat (Seerat Studies, 2023)
According to Quran and Sunnah, the responsibility of grooming the Children in respect of their physical and spiritual needs from very initial stages of their life such as infancy till childhood and teenage rests on the shoulders of their parents and guardians. Providing the proper and timely opportunities of knowledge and training can also be considered also on these responsibilities. This article intends to analyse the role of parents in the upbringing and grooming of their children from the initial phases of their life such as infancy and childhood till teenage and further stages of their life in the light of the Sunnah of the prophet (s.a.w) by tracing practical examples from the life of the prophet (s.a.w) in this regard. Keywords: Education, upbringing, grooming, Responsibility, Family